Determinación de las áreas improductivas para el establecimiento de agricultura urbana en el barrio san Felipe del cantón Latacunga, provincia Cotopaxi- 2021. - Pontón Jines, Joselyn Liliana (2021)
The agronomy major of the Agricultural Sciences and Natural Resources School of the Technical University of Cotopaxi, has designed a proposal of urban agricultural production to encourage people to produce their own food in a sustainable way. This case study was carried out in San Felipe neighborhood located in Eloy Alfaro parish of Latacunga city, Cotopaxi Province, with UTM coordinates longitude: 763453.78 and latitude: 9898534.69 at an altitude of 2790 meters above sea level. This bibliographic study was carried out with the purpose of determining the unproductive areas and creating an urban agriculture proposal for the sector. Through the bibliographic research, information was gathered on how to propose an urban garden with vegetables that are adapted to the climatic conditions of the sector and the benefits of urban agriculture. Likewise, information was sought on organic fertilizers, biopreparations, biological pest control, crop association and, as a suggestion for application, organic compost, since it was concluded that it would bring benefits to the sector by being able to recycle vegetable waste from their homes. To do this, the geographical coordinates of the area under study were taken using the geographic information system with Google Earth and Google Earth Pro software. With which maps were created in the ArcGis program and it was determined that the total free or unproductive areas of the area is (13 hectares or 130,000m2) and finally a proposal was made based on the establishment of urban vegetable gardens using the association of crops, organic compost, biological corridors, Bioinsecticide (alcoholic extract of garlic and chili), Biofungicide (horsetail), Biofertilizer (dung tea). In a minimum area from 2m2 to 264m2 in Barrio San Felipe.